Bacterial Translocation Associates With Aggression in Schizophrenia Inpatients - Wang, Chong; Zhang, Teng; He, Lei; Fu, Ji-Yong; Deng, Hong-Xin; Xue, Xiao-Ling; Chen, Bang-Tao (Frontiers in Systems Neuroscience, 2021)
Objective: Accumulating evidence indicates that inflammation abnormalities may contribute to aggression behaviors in psychotic patients, however, the possible sources of inflammation remain elusive. We aimed to evaluate the associations among aggression, inflammation, and bacterial translocation (BT) in aggression-affected schizophrenia (ScZ) inpatients with 2 weeks of antipsychotics discontinuation. Methods: Serum specimens collected from 112 aggression and 112 non-aggression individuals with ScZ and 56 healthy adults were used for quantifications of inflammation- or BT-related biomarkers. Aggression severity was assessed by Modified Overt Aggression Scale (MOAS). Results: Proinflammation phenotype dominated and leaky gut-induced BT occurred only in cases with ScZ with a history of aggression, and the MOAS score positively related to levels of C-reactive protein, interleukin (IL)-6, IL-1β, and tumor necrosis factor-α. Furthermore, serum levels of BT-derived lipopolysaccharide (LPS), as well as LPS-responded soluble CD14, were not only positively correlated with levels of above proinflammation mediators but also the total MOAS score and subscore for aggression against objects or others. Conclusion: Our results collectively demonstrate the presence of leaky gut and further correlate BT-derived LPS and soluble CD14 to onset or severity of aggression possibly by driving proinflammation response in inpatients with ScZ, which indicates that BT may be a novel anti-inflammation therapeutic target for aggression prophylaxis.